Kinematics in ultra-precision grinding of WC moulds. (1st January 2011) - Brinksmeier, Ekkard; Riemer, Oltmann; Rickens, Kai; Meiners, Kathrin
The target of this paper is the evaluation of process kinematics in ultra-precision grinding for the manufacturing of typical precision glass moulds (diameter 5 mm to 20 mm) with respect to part quality (form accuracy, surface roughness), machining time and process stability. This is discussed exemplary for two specific grinding kinematics by comparison of experimental results regarding achievable figure accuracy and surface finish.